Penerapan Kegiatan 7 Kebiasaan Anak Indonesia Hebat sebagai Strategi Pengembangan Karakter Anak Usia Dini di TK Sartika - Annisa Fahmi Mannassai; Siti Marwah Mustapa; Intan Nuraini Lamanasa; Enjel Sukma; Putri Rahmadani Lahaji (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Early childhood education is an important foundation in character building, because the golden age is a period when physical, cognitive, and socio-emotional development occurs very rapidly, requiring planned and continuous stimulation. One effort that can be made is through the implementation of G7KAIH activities, which is a program of seven positive habits designed to instill the values of independence, discipline, cooperation, cleanliness, and responsibility from an early age. This study aims to describe the implementation of G7KAIH as a strategy for character development in early childhood at Sartika Kindergarten. The method used is descriptive qualitative with data collection techniques in the form of semi-structured interviews with teachers directly involved in the program implementation. The results show that G7KAIH has been integrated into daily routines, although it is still in its early stages and does not yet have standard operating procedures. The children's responses varied; some were enthusiastic, but others still needed guidance due to differences in their social-emotional development. The obstacles that arose were related to the children's understanding and the limitations of the implementation guidelines, but these could be overcome through motivation and a variety of activities. Overall, G7KAIH made a positive contribution, especially to the children's independence and discipline.